Lesion of the subthalamic nucleus for the alleviation of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced parkinsonism in the primate. - Aziz, T; Peggs, D; Sambrook, M; Crossman, A (1991)
Central to the neural mechanism of MPTP-induced parkinsonism is overactivity of the subthalamic nucleus. Lesion of the subthalamic nucleus has therefore been performed in two primates with this condition and found to produce a remarkable amelioration of the disorder.